GELIAT NELAYAN PANTAI AYAH KEBUMEN MENGHADAPI KRISIS EKONOMI 1998-1999 - Romadi, Romadi (Faculty of Social Science, Universitas Negeri Semarang, 2013)
In 1997-1999, Indonesia experienced economic crisis beginning with the monetary crisis, which led to the paralysis of the economy of most communities. Fishermen of Pantai Ayah is a group of people who can not be separated from the economic crisis that hit Indonesia. Based on this research, it is known that fishermen suffered due to rising prices of basic needs, while their income from the sea did not increase significantly. The income they got are not comparable with the fishing capital they spent, making it difficult to meet the daily needs of the family. Fishermen make every effort to keep the family’s needs remain unmet, including by seeking a second job, borrow money and sell goods. In addition, the social capital of trust and honesty is an important factor in facilitating the process of nyelang (borrow money in a short time returning) and debt. Government assistance received by the community to reduce the impact of the economic crisis, is Market Operations.